The analysis of teaching belief between English lecturers at the Faculty of Economics and Business (FEB) and Faculty of Teacher Training and Education (FKIP) in the University of Lampung (Unila) - Lidya Ayuni Putri; Rafista Deviyanti; Sri Suningsih (Universitas Lampung, 2021)
Teaching is a dynamic process that involves a quick decision-making process and is also an activity that refers to what students need. This decision-making process often appears as a reflection of what the teacher believes and also as a reflection of the theory adopted by the institution where the teacher works. This can then be said as evidence to claim that the concept (belief) that is believed by the teacher influences the decisions about learning practices and influences the activities that the teacher does in the classroom. Every teacher has belief as a basic reference that they believe in teaching as well as a reference for overcoming obstacles that occur in the teaching and learning process in the classroom. This study will examine whether there is a difference between perceptions language teacher of English in the Faculty of Economics and Business and the Faculty of Teacher Training and Education in Unila. This study uses English lecturer as the sample from two different faculties in Unila. The questionnaire is distributed to selected respondents and will then be analyzed descriptively and qualitatively.Keywords: Teaching belief, perception, English Lecturer, EFL.